Campements mésolithiques en Bresse jurassienne Choisey et Ruffey-sur-Seille - Séara, Frédéric; Rotillon, Sylvain; Cupillard, Christophe (Documents d'archéologie française, 2002)
A combination of paleo-environmental and archaeological analytical methods has provided information on Ruffey and Choisey-sur-Seille, two open-air sites from the Mesolithic period. It has thus been possible to determine the environmental framework of the camps. Study of finds distribution, stone-tool industry, the origins of flint raw materials and faunal remains has enabled archaeologists to reconstruct the camps' spatial organisation and to better de fine the cultural identity of hunter groups Excavations at Ruffey produced a significant discovery one of the oldest cremation burials from the middle Sauveterrian. Evidence of different cultural groups passing through the Bresse area of the Jura confirms the Franche- Comlé's rote as a crossroads.